Analysis of Labor Productivity in Bricklaying Operation of Building Construction in Surkhet, Nepal - Bijay Rana,; Socrates Bhattarai Sharma,; Uttam Neupane,; Santosh Kumar Shrestha, (Advances in Engineering and Technology: An International Journal, 2023)
The development of the nation’s infrastructure depends heavily on the construction industry. The entire labor productivity during the project has a significant impact on construction productivity. Therefore, it is necessary to investigate the origins and consequences of labor productivity in the context of the Nepalese construction industry. The methodology involved in conducting the research is the formation of the problem statement, developing research objectives, literature review, data collection, data analysis, conclusion, and recommendations. The data for this research is collected by a literature review as well as a questionnaire and physical observations of building construction. The literature review helped to identify several elements that have an impact on labor productivity. To determine the factors that influenced labor productivity the most, a questionnaire survey was undertaken with a Likert scale. The required information was then produced by processing, analyzing, and interpreting the data using Microsoft Excel and SPSS software tools. The Cronbach’s Alpha value was computed using SPSS to measure the internal consistency and found to be 0.976 which shows the better reliability of the research and data collection. From the study, we can conclude that the results obtained from the relative importance index (RII), mean response analysis (MRA), and sensitivity analysis through Artificial Neural Network (ANN) meets the same conclusion as the highest influencing factor affecting labor productivity is ‘Material related factors’ followed by ‘Leadership related factors’, ‘Manpower related factors’, and the last ‘Other factors’.